SHOULD A COMPANY’S DIGNITY BE PROTECTED UNDER SECTION 10 OF THE CONSTITUTION? THE QUESTION IN Reddell v Mineral Sands Resources (Pty) Limited [2022] ZACC 38 - Minenhle Alfred Nzimande; Razaana Denson; Joanna Botha (Obiter, 2024)
In Reddell v Mineral Sands Resources (Pty) Ltd ([2022] ZACC 38) (Reddell), the Constitutional Court considered whether section 10 of the Constitution of the Republic of South Africa, 1996 (the Constitution), as read with section 8(4), should be interpreted to protect the dignity of juristic persons (in this case, mining companies). The majority and minority judgments arrived at conflicting decisions on the point. Unterhalter AJ, for the minority, held that juristic persons should be protected under section 10, while Majiedt J, for the majority, held otherwise. The majority also developed the common law of defamation to limit the circumstances in which a juristic person may succeed in a claim for general damages for non-patrimonial loss. The authors make two claims. First, it is argued that the minority judgment correctly interpreted the nature and purpose of section 10 (the guarantee of human dignity) when read with section 8(4) of the Constitution, which provides that juristic persons are entitled to bear the rights in the Bill of Rights as required by the nature of the right and the nature of the juristic person in issue. It is asserted that the two sections can be interpreted to entitle companies to rely on section 10 of the Constitution to protect their right to dignity, encompassing their good name and reputation. Secondly, it is argued that the majority’s development of the common law of defamation – to create a special exception for cases where a juristic person sues for general damages – was unnecessary, and has created legal uncertainty. The case note proceeds as follows. First, the authors introduce the facts of the case, and then explore the ratione decidendi of both judgments. Secondly, the note addresses the ambit and scope of human dignity as a constitutional right, followed by the applicable principles governing constitutional interpretation, including the role of the heading of a statutory provision. This is followed by a discussion of the law of defamation concerning whether a juristic person can claim damages for an infringement to its reputation under the actio iniuriarum. The legal position prior to the judgment in Reddell is compared to that which now applies. Finally, the decision is evaluated with reference both to the reasoning used by the majority and minority respectively and the significance of the outcome of the case for our law. A detailed discussion of the constitutionality of awarding general damages to corporations for defamation on the basis that such claims unjustifiably limit section 16 of the Constitution (the right to freedom of expression) falls outside the scope of this case note.